Observations of broadband solar UV-A irradiance at Santa Maria, Brazil (29°S, 53° W) - S. Okano; K. Makita; N. J. Schuch; E. Echer (Geofísica Internacional, 2004)
Observations of broadband solar UV-A irradiance (320-400 nm) were made at Santa Maria, Brazil (29° S, 53° W) between September 1993 and December 1996. Two different measurement techniques were used, the direct sun (DS) with the sensor pointed directly to the sun, and the zenith sky (ZS), with the sensor pointed to the zenith. The seasonal variation of UV-A DS and ZS irradiances measured at local noon is analysed. Both UV-A DS and ZS irradiances have a strong seasonal variability, anti-correlated to the solar zenith angle variation. It is shown that UV-A ZS irradiance has a larger seasonal variation than UV-A DS irradiance, with summer/winter ratios of 3.4 for UV-A ZS and 1.4 for UV-A DS. This difference is explained because of the geometrical arrangement of the observations; UV-A DS irradiance is measured tracking the sun and its variability is due to the atmospheric optical path variation during the year. UV-A ZS irradiance is diffuse irradiance measured pointing at a fixed direction, the zenith, and besides the atmospheric optical path variability, the component of direct irradiance incident on the horizontal surface has also a variation with solar zenith angle. Analysing UV-A DS and ZS irradiances versus solar zenith angle, it was observed that UV-A ZS decreases faster with higher solar zenith angles than UV-A DS. Calculations using Beer’s law at 370 nm were made and show similar behaviour for irradiances at a horizontal surface, compared to UV-A ZS, and at a surface perpendicular to the solar beam, compared to UV-A DS irradiance.